PENGEMBANGAN PERANGKAT PEMBELAJARAN PADA MATAKULIAH STATISTIKA DASAR DENGAN METODE PROBLEM BASED LEARNING - Krisdiana, Ika (JEMS Jurnal Edukasi Matematika dan Sains, 2016)
The purpose of this research is the development of learning in basic statistics courses with Problem Based Learning method. This research is the development that follows the mechanism and design of the development of teaching materials (Fenrich, 1997). The steps include the development of teaching materials analysis phase (analysis), planning (planning), design (design), development (development), implementation (implementation), evaluation and revision (evaluation and revision). The initial phase of the study in the first year is to develop an instrument for the investigation, analysis (analysis), planning (planning) and designing (design) prototype. In this study, the learning device that has been designed include: Syllabus, SAP, Student Worksheet, and Textbook of Basic Statistics.The results of this study are learning the basic statistics covering the syllabus, SAP, Worksheet Student and Instructional Materials. From the results of the study showed that the learning tools that have been developed can be regarded as a good learning tool because it meets the criteria of validity, practicality, and effectiveness.